Neural Epidermal Growth Factor-Like Like Protein 2 Is Expressed in Human Oligodendroglial Cell Types - Shaker, Mohammed R.; Kahtan, Amna; Prasad, Renuka; Lee, Ju-Hyun; Pietrogrande, Giovanni; Leeson, Hannah C.; Sun, Woong; Wolvetang, Ernst J.; Slonchak, Andrii (Frontiers in Cell and Developmental Biology, 2022)
NELL2 is a cytoplasmic and secreted glycosylated protein with six epidermal growth factor-like domains. In animal models, Nell2 is predominantly expressed in neural tissues where it regulates neuronal differentiation, polarization, and axon guidance, but little is known about the role of NELL2 in human brain development. In this study, we show that rostral neural stem cells (rNSC) derived from human iPSC exhibit particularly strong NELL2 expression, and that NELL2 protein is enriched at the apical side of neural rosettes in hiPSC derived brain organoids. Following differentiation of human rostral NSC into neurons, NELL2 remains robustly expressed but changes its subcellular localization from >20 small cytoplasmic foci in NSC to 1-5 large peri-nuclear puncta per neuron. Unexpectedly, we discovered that in human brain organoids NELL2 is readily detectable in oligodendroglia and that the number of NELL2 puncta increases as oligodendrocytes mature. Artificial intelligence-based machine learning further predicts a strong association of NELL2 with multiple human white matter diseases, suggesting that NELL2 may possess yet unexplored roles in regulating oligodendrogenesis and/or myelination during human cortical development and maturation.